Hope and dread in Montana literature - Egan, Ken, 1956- (Western literature series., 2003)
"Egan's objective, in this survey of Montana's literary history, is to demonstrate the roots of the state's literature in its conflicted history and complex mixture of racial and ethnic traditions and, at the same time, to offer the possibility of thoughtful solutions to the West's daunting social and environmental dilemmas through the insights of some of the state's best writers. From the narratives of early explorers and ranchers, Native Americans, and settler women through the works of such major twentieth-century luminaries as A.B. Guthrie and Ivan Doig, Egan traces the evolution of Montanans' early fantastic dreams of economic, religious, and cultural success into failure and despair, violence and tragedy. Yet, side by side with these tales of woe are tales of endurance and even triumph, evidence of the strength and creative potential of the state's people."--Jacket